The Influence Of Organizational Culture, Work Stress, And Workload On The Performance Of Civil Servants At Public Health Centers In Mukomuko Regency - Anggara, Agil; Suwarni, Suwarni; Soleh, Ahmad (UNIVED Press, 2026)
This study aims to examine the influence of organizational culture, work stress, and workload on the performance of civil servants at public health centers (Puskesmas) in Mukomuko Regency. A quantitative explanatory approach was applied, involving 263 respondents from 17 active Puskesmas as the research sample. Data were collected through questionnaires that had been tested for validity and reliability, ensuring the accuracy and consistency of measurement. The multiple linear regression analysis revealed that organizational culture and workload have a positive and significant effect on employee performance, while work stress does not show a significant impact. The coefficient of determination (R²) value of 0.692 indicates that 69.2% of performance variations can be explained by the three independent variables, while the remaining 30.8% is influenced by other factors outside the model. The findings emphasize that a strong organizational culture and balanced workload are key drivers of performance improvement in public health organizations. Meanwhile, stress at an adaptive level can be managed effectively without reducing work outcomes. These results offer managerial insights for strengthening employee performance in government health institutions.